A trial of evaluation based on multiplicative multivariate model for non-stationary road traffic noise - M. OHTA; Y. FUJITA (Archives of Acoustics)
Since the non-stationary fluctuation of actual acoustic environment like the road traffic noise within a long time interval is usually caused not by the change of merely additional external noise but by the essential change of internal factors themselves, it is reasonable to give as a mathematical model of this non-stationary fluctuation not an additive model but a multiplicative model. In this paper, mainly from a methodological viewpoint, first, the characteristic function method of Mellin transform type for the above multiplicative model is introduced and a new unified expression form of the probability density function within a long time interval is derived in an expansion form based on the probability density function within a short time interval of local stationary type as its first expansion term with distribution parameters reflecting hierarchically various types linear and nonlinear correlation information.